Suprabenthic assemblages from the Capbreton area (SE Bay of Biscay). Faunal recovery after a canyon turbidity disturbance. (December 2017) - Frutos, Inmaculada; Sorbe, Jean Claude
Abstract: In the Capbreton area, suprabenthic assemblages were sampled with a sledge towed over the bottom, at different sites located within the upper part of a 'gouf-type' canyon (8 hauls between 642 m and 797 m, on the axis of the thalweg or on flat perched flank terraces such as site K), on the northern adjacent open slope (2 hauls between 500 and 567 m) and on the northern adjacent shelf margin (2 hauls between 151 m and 158 m). A multivariate analysis carried on the faunal data discriminated different assemblages in this area: a near-canyon shelf assemblage (55 species, mainly amphipods and decapods; 3496 ind./100 m 2, 40% mysids; dominant species: Nyctiphanes couchii, Leptomysis gracilis, Weswoodilla rectirostris, Anchialina agilis, Scopelocheirus hopei and Philocheras bispinosus ); an open slope assemblage (111 species, mainly amphipods and isopods; 249 ind./100 m 2, 36% amphipods; dominant species: Disconectes phalangium, Munnopsurus atlanticus and Boreomysis arctica ); a canyon E assemblage (129 species, mainly amphipods, mysids and cumaceans; 1172 ind./100 m 2, 58% amphipods; dominant species: Melphidippa sp. B, Chelator insignis ); a canyon E' assemblage (107 species, mainly amphipods and mysids; 507 ind./100 m 2, 73% amphipods; dominant species: Cleonardopsis carinata, Bonnierella abyssorum, Rhachotropis caeca and Arcturopsis giardi ); and a temporary canyon assemblage at site K (34 species, mainly amphipods and mysids; 899 ind./100 m 2, 85% amphipods; dominant species: Tmetomyx similis, Caeconyx caeculus, Nebalia sp. A and Cleonardopsis carinata ). Site K was sampled only four months after a turbidity event, detected on sediment cores (18 cm thick Bouma sequence) taken during the same cruise and triggered by the violent storm ('ouragan Martin', wind up to 200 km/h) which affected the French Atlantic coast on 27 December 1999. The corresponding suprabenthic assemblage showed evidence of deep structural changes after this catastrophic event, characterized by relative low values of species richness and diversity indices and by the exceptional dominance of opportunistic pioneer colonizers such as the scavenger Tmetonyx similis (61% of total density). Partial assemblage recovery was noticed 18 months after the turbidite deposition, attested by higher values of structural indices and by the inclusion of the corresponding sample within the climax canyon assemblage cluster. Highlights: Description of the deep suprabenthic assemblages from the upper Capbreton Canyon. Impact of a turbidity event in a canyon triggered by a storm. Faunal recovery of impacted suprabenthic assemblages after a turbidite.